STUDIES ON HYDATIDOSIS IN SHEEP AND GOATS AT LAHORE, PAKISTAN - H. J. Iqbal; A. Maqbool; M. Lateef; M. A. Khan; A. Riaz; A. Mahmood; F. A. Atif; Z. Ali M. S. Ahmad (Journal of Animal and Plant Sciences, 2012)
The aim of present study was to observe the current status of hydatidosis in small ruminants at Lahore. A total of 4800 animals comprising 2400 sheep (784 hoggets and 1616 adults) and 2400 goats (561 young, 1839 adults) of both sexes were examined at Lahore abattoir during slaughtering from March 2010 to February 2011. In sheep, 14 (1.79 %) hoggets including 12 (1.78%) males and 2 (1.80 %) females and 184 (11.38%) adult sheep including 139 (11.12%) males and 45 (12.30%) females were infected. 6 (1.06%) goats comprising 4 (0.87%) males and 2 (1.94%) females under one year of age and 143 (7.77 %) above one year having 99 (7.58%) males and 44 (8.25%) females were found infected with hydatidosis. Overall prevalence in sheep was 8.85% and 6.21% was in goats. During postmortem, the organs like lungs, liver, heart, spleen and abdomen & thoracic cavity were examined. [In both sexes of sheep, the mean percentage of organ distribution of hydatid cyst was recorded as [45.19 % lungs], [33.91 % liver], [19.55 % lungs and liver in situs], [2.06 % heart], [2.39 % spleen], and [6.9 % abdomen and thoracic cavity]. The mean of organ distribution of hydatid cyst in goats was recorded as 34.38 % lungs, 40.56 % liver, 16.95 % lungs and liver in situs, 0.49 % spleen and 7.63 % abdomen and thoracic cavity. In sheep, highest infection was observed in lungs whereas liver was most infected organ in goats. No seasonal variation was observed in the prevalence of hydatidosis in sheep and goats throughout the year. Fertility of hydatid cysts removed from liver and lungs of sheep and goats were studied and it was found that apparently hepatic cysts were more fertile as compared with the pulmonary cysts in both the species but the difference was not significant (P = 0.87).
Keywords: [Hydatidosis; sheep; goats; Lahore].